Clamping deformation analysis and machining parameter optimization of weak stiffness ring parts. (March 2019) - Zhang, Chengyan; Jiao, Sicheng; Wang, Lixin
Abstract: A series of turning experiments have been carried out to study the effect of different cutting speed, feed rate, pre-tightening torque and clamping mode on deformation during turning of weak stiffness ring parts. The roundness error of workpiece is measured by using a coordinate measuring instrument, and the roundness error is evaluated by using the least square circle method. The influence of various cutting parameters and clamping mode on the turning deformation of weak stiffness ring parts is analysed. The distribution of residual stress along depth direction was measured by X-ray diffraction method layer by layer. The optimization model of machining process parameters is established. MATLAB is used to solve the optimization model based on the multi-objective optimization function of genetic algorithm, optimizing cutting parameters including clamping force.